Butyrate drives the acetylation of histone H3K9 to activate steroidogenesis through PPARγ and PGC1α pathways in ovarian granulosa cells. Issue 2 (12th January 2021) - Ye, Qianhong; Zeng, Xiangfang; Wang, Shuai; Zeng, Xiangzhou; Yang, Guangxin; Ye, Changchuan; Cai, Shuang; Chen, Meixia; Li, Siyu; Qiao, Shiyan
Abstract: Maintaining ovarian steroidogenesis is of critical importance, considering that steroid hormones are required for successful establishment and maintenance of pregnancy and proper development of embryos and fetuses. Investigating the mechanism that butyrate modulates the ovarian steroidogenesis is beneficial for understanding the impact of lipid nutrition on steroidogenesis. Herein, we identified that butyrate improved estradiol and progesterone synthesis in rat primary ovarian granulosa cells and human granulosa KGN cells and discovered the related mechanism. Our data indicated that butyrate was sensed by GPR41 and GPR43 in ovarian granulosa cells. Butyrate primarily upregulated the acetylation of histone H3K9 (H3K9ac). Chromatin immune‐precipitation and sequencing (ChIP‐seq) data of H3K9ac revealed the influenced pathways involving in the mitochondrial function (including cellular metabolism and steroidogenesis) and cellular antioxidant capacity. Additionally, increasing H3K9ac by butyrate further stimulated the PPARγ/CD36/StAR pathways to increase ovarian steroidogenesis and activated PGC1α to enhance mitochondrial dynamics and alleviate oxidative damage. The improvement in antioxidant capacity and mitochondrial dynamics by butyrate enhanced ovarian steroidogenesis. Collectively, butyrate triggers histone H3K9ac to activate steroidogenesis through PPARγ and PGC1α pathways in ovarian granulosa cells.